Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPS Menggunakan Model PBL di Kelas V SD - Rivai, Maulidia Syofia; Nasrul, Nasrul; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to improved the learning outcomes of student in Social Science Knowledge used PBL on 5th grade elementary school. Types of this research were 25 people consist of 12 men and 13 women. The implementation of this research was conducted in two cycles with research procedure that consist of planning, implementation, observation and reflectio. The results showed an increase in terms of (a) the RPP of cycle I with an average of 75% to 89,28% in cycle II, (b) Implementation teacher’s activity cycle I with an average 83,92% to 92,85% in cycle II, while for the implementationon the students cycle I with an average 80,35% to 92,85% in cycle II, (c) Students learning outcomes in cycle I with an average of 77 be 87,3 in cycle II. It can be concluded that used PBL model can improve students achievement in Social Science Knowledge of 5th grade elementary school at SDN 31 Jati Padang.Keyword : Learning outcomes, Social science, PBL